HSBA Handbook on Ship Finance
XXIX, 384 p. 80 illus., 16 illus. in color.
Keywords: This book is a major work that focuses exclusively on ship finance and includes contributions on the increasingly complex field of ship finance, which has over the last two decades become a key aspect in the world of shipping and ship owning. The book offers an enlightening mix of theoretical analysis and well-founded practical insights into the daily markets. Given that ship finance continues to develop dynamically around the world, the book covers subjects ranging from the German KG market to Islamic Finance, from loans to legal aspects and from asset pricing to risk management.